Development of Problem Based Student Worksheets to Improve Students Critical Thinking Ability - Ritonga, Novi Rahmadani; Sitorus, Masganti; Afri, Lisa Dwi (Yana Research, 2022)
This study aims to develop mathematics teaching materials in the form of problem based student worksheets on geometry row material and also aims to find out the effectiveness and practicality of student worksheets which is developed in improving students critical thinking skills for grade XI MA/SMA. This research was conducted in class XI IPA 6 MAN 2 Model Medan, with the type of research and development and 4D development model (Define, Design, Develop, dan Dessiminate). The research instruments used are validation by experts, questionnaires of student responses and test of learning outcomes after and before learning using the developed product. The problem-based student workshets developed in this study were declared valid by validator and field trials were carried out to see their effectiveness and practicality. The result obtained from validators is 78% for validator I those in the category are worthy of use, and for validator II obtained a percentage of 93% who entered the category of eligible to use and 100% percentage obtained from the media expert validator. Then the problem-based student worksheet developed is declared false and entered in the ccategory worthy of use. The problem-based student worksheet developed was also stated to be practical with a practicability test percentage of 77%. The problem-based student worksheet developed has met the effective criteria based on the percentage of classical learning completeness of 80% with the results of 75% which means that the problem-based student worksheet developed is in the category quite effective.